2023
DOI: 10.3389/fbioe.2023.1283898
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Zinc oxide nanoparticles from Celosia argentea: toward improved antioxidant, antibacterial, and anticancer activities

Rana Abdullah Alghamdi,
Maryam Hassan Al-Zahrani,
Lamaia R. Altarjami
et al.

Abstract: Biogenic Zinc oxide (ZnO) nanoparticles (NPs) were synthesized from Celosia argentea (C. argentea) plant extract. Structural analysis confirms the successful synthesis of biogenic zinc oxide NPs from C. argentea extract. The biogenic ZnO NPs have an average particle size of 21.55 ± 4.73 nm, a semispherical shape, and a specific surface area of about 50 m2/g. The biogenic ZnO NPs have a powerful radical scavenging activity (Ic50 = 91.24 mg/ml) comparable to ascorbic acid (ASC) as a standard (Ic50 = 14.37 mg/ml)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…These results align with the findings of Akbar et al, 55 who reported robust antibacterial effects of ZnO-NPs against Salmonella typhimurium and S. aureus . 58 60 Moreover, other studies have demonstrated the potent bactericidal and antifungal activities of ZnO-NPs against a spectrum of pathogens. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…These results align with the findings of Akbar et al, 55 who reported robust antibacterial effects of ZnO-NPs against Salmonella typhimurium and S. aureus . 58 60 Moreover, other studies have demonstrated the potent bactericidal and antifungal activities of ZnO-NPs against a spectrum of pathogens. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%